Complete plastome of Toricellia tiliifolia (Toricelliaceae), a relict plant. Issue 1 (2nd January 2019) - Liu, Changkun; Yang, Lifang; Yang, Zhenyan; Ji, Yunheng
Abstract: In this study, we presented the first complete plastome of Toricellia tiliifolia, an Arcto-Tertiary relict endemic to eastern Asian, using Illumina pair-end sequencing data. The plastome was 158, 627 bp in length and consisted of a pair of inverted repeats (IRs 26, 174 bp), which were separated by a large single-copy region (LSC 87, 847 bp) and a small single-copy region (SSC 18, 432 bp). The plastome harbored 114 unique genes, including 80 protein-coding genes, 30 tRNAs, and 4 rRNAs. Phylogenetic analysis indicated that T. tiliifolia was the earliest diverged clade within the order Apiales.